Dry needing in the treatment of myofascial pain associated with temporomandibular dysfunction: a systematic review (Research, Society and Development, 2021)
Myofascial pain is a muscle disorder that is often associated with temporomandibular disorders, affects the masticatory muscles and can lead to functional limitations. This systematic review aims to identify the scientific literature on the effects of superficial and deep dry needling for the treatment of pain in patients with myofascial temporomandibular disorder (TMD). This is a systematic review seeking primary studies in the PubMed and Virtual Health Library - VHL databases (combining databases such as LILACS - Latin American and Caribbean Literature in Health Sciences, MEDLINE - Medical Literature Analysis and Retrieval System Online, SciELO - Scientific Electronic Library Online, among others) with the descriptors “temporomandibular joint disorders dry needling”, or “myofascial temporomandibular dysfunction dry needling”, or “temporomandibular dysfunction dry needling”, as well as articles in English, Portuguese or Spanish that respond the guiding question of the use of dry needling in the treatment of myofascial TMD were included; theses, monographs, treatment associations, articles that were in languages other than those mentioned above, and systematic reviews were excluded. Nine studies were considered eligible. One study compared superficial and deep dry needling. Four studies used only deep dry needling and another 4 studies did not specify the type of needling used. Therefore, the results found suggest that there is not enough data to draw solid conclusions about which type of dry needling is best for the treatment of myofascial pain associated with TMD. Low risk of bias randomized controlled trials are strongly needed.